화천군 농촌 어메니티 자원 및 농가 경영실태 조사를 통한 농촌정책 중장기 방향 연구 - 송미령 (한국농촌경제연구원, 2008)
The purpose of this research is to derive long-run policy directions of agricultural?rural development in Hwacheon with survey of rural amenities and farm household economies. The major results will be divided as two parts. One is to utilize and connect each marketable resource with the categorization and characterization of regional amenities. The other one is to categorize farm households with respect to situation of farm managements and economies and propose differentiated policy programs to each categorized farm household. The representative rural amenities in Hwacheon could be categorized as regional festivals that many urban visitors want to participate, externally well-known resources, and rural tourism villages established by rural-urban interchanges. They could be summarized as follows; “Sancheoneo Festival”, “Tomato Festival”, “Wha-ak Mountain”, “Kwang-duk Valley”, “Kok-un-Koo-gork”, “Togomi Village”, “Peace Dam”, “Boong-eo Island”, “Paro Reservoir” etc. There were not so much differences in characteristics of amenities by each village except representative villages in rural-urban interchanges, for example, Sindae-ri, and Kwng-duk ri. “Jazz festival on the ridge of between paddies filed” at Sindae-ri that is the representative village in rural-urban interchanges has enlarged to nearby villages including Goowoon-ri and Jangchon-ri, and improves networks between villages. “Tomato Festival on Kwang-duk ri” also enlarged its scopes and networks between villages. With respect to discovering and merchandizing amenity resources, we could summarize the characteristics of amenity resources as follows; Concrete recognitions and public relations of diverse activities on the rural-urban interchange, and the small size festivals were not gotten accomplished except a few rural tourism village. The meaning, historical momentum and differentiation of amenity resources was neglected and not linked to a specific storytelling even though introduction itself of individual facilities and resources was done. Furthermore, village people’s recognition of historical and cultural resources was quite low and there were big differences of recognitions about the representative amenity resources of Hwacheon between the public and the resident. The recognition of amenity resources between the residents and the non-residents was big differentiated. Villages with higher-income farm households focusing on special agricultural products were not interested on developing amenity resources. Major coming tasks of utilizing amenity resources could be to discover amenity resources and to reinforce and diversify the utilization policy with regard to village characteristics. Human capital of farm manages in Hwacheon could be summarized as follows; the younger and more educated were managing the farm household compared to the average of the national wide and the Gangwon Province. Therefore the type of farming in Hwacheon was more leaned to cash crops and the portions of full time farming were higher than the average figures of the national wide and the Gangwon province. To identify the competitiveness of farm household and categorize farm households for customized supports, index of farm household’s potentiality was invented in terms of human capital, scale of management, social capital and the opportunity to off-farm activities. Index of farm household’s potentiality was calculated by individual farm household level and grouped to regions (Up and Myon). According to the index, farm households in Hwacheon could be grouped to the upper level, the semi-upper level, the semi-lower level, and the lower level. The policies customized were recommended by each category. We recommended the agricultural and rural development policy in Hwacheon in terms of the amenity resources and the category of farm households. Not only should the customized agricultural policy be connected to amenity resources, but also the development of regional amenity should consider the type of farm household. Researchers: Mi-Ryung Song, Kyeong-Duk Kim, Joo-In Seong, Min-Soo Kang E-mail address: mrsong@krei.re.kr